"What They Had between Their Legs Was a Form of Cash": Homosexuality, Male Prostitution, and Intergenerational Sex in 1950s Italy. Issue 1 (1st March 2020) - Ponzio, Alessio
Abstract: This article, showing how ubiquitous male youth prostitution was in 1950s Italy, exposes the pederastic and (homo)sexual vivacity of this decade. Moreover, this article also suggests that even if police, the media, and medical institutions were trying to crystallize a rigid chasm between homo- and heterosexuality, there were still forces in Italian society that resisted such strict categorization. The young hustlers described by contemporary observers bear witness to the sexual flexibility of the 1950s in Italy. These youths inhabited queer spaces lacking a clear-cut hetero–homo divide, spaces where "modern" sexological categories and identities had not yet entered. Prior to the mass circulation of rigid sexual labels, it was still possible for many Italian boys, youths, and young men to dwell in liminal queer spaces. The exchange of money purified their acts, guaranteed their maleness, and effaced potential stigmatization.